1982
DOI: 10.1246/cl.1982.261
|View full text |Cite
|
Sign up to set email alerts
|

Rh(I) COMPLEXES CONTAINING FULLY ALKYLATED MONO- AND DIPHOSPHINE LIGANDS AS HIGHLY ACTIVE HYDROGENATION CATALYSTS FOR CARBONYL COMPOUNDS

Abstract: Our search for highly active hydrogenation catalysts for carbonyl compounds, starting with neutral Rh(I) hydride complexes, [RhH(PR3)n] (R=i-Pr, n=3; R=Cy, n=2), has led to the discovery of cationic Rh(I) complexes with fully alkylated diphosphine ligands, [Rh{(i-Pr)2P(CH2)nP(i-Pr )2}(NBD)]C104 (n=3,4). These compounds prove to be versatile and efficient for hydrogenation of a variety of carbonyl compounds, including aldehydes.A number of rhodium complexes, e.g., neutral rhodium(I) complexes of Wilkinson type,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…[6] Later, RuCl 2 (PPh 3 ) 3 was used as hydrogen transfer catalyst, [7] and in 1991 it was reported that the addition of small amounts of base had a dramatic effect in the RuCl 2 (PPh 3 ) 3 -catalyzed transfer hydrogenation of ketones giving a rate enhancement of about 10 3 to 10 4 times. [8] Also, (phosphane)rhodium(I) complexes can catalyze the transfer hydrogenation of aldehydes and ketones by 2-propanol, [9] and it was found that base also accelerates these reactions, [10] but not to the same extent as the RuCl 2 (PPh 3 ) 3 -catalyzed transfer hydrogenations. [8] To make the Rh system more favorable for scale-up, we heterogenized Wilkinson's catalyst on an easily available solid support to become recyclable.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Later, RuCl 2 (PPh 3 ) 3 was used as hydrogen transfer catalyst, [7] and in 1991 it was reported that the addition of small amounts of base had a dramatic effect in the RuCl 2 (PPh 3 ) 3 -catalyzed transfer hydrogenation of ketones giving a rate enhancement of about 10 3 to 10 4 times. [8] Also, (phosphane)rhodium(I) complexes can catalyze the transfer hydrogenation of aldehydes and ketones by 2-propanol, [9] and it was found that base also accelerates these reactions, [10] but not to the same extent as the RuCl 2 (PPh 3 ) 3 -catalyzed transfer hydrogenations. [8] To make the Rh system more favorable for scale-up, we heterogenized Wilkinson's catalyst on an easily available solid support to become recyclable.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of hydrogenation rates, perusal of the literature indicates that a certain degree of backbone flexibility (larger available bite angle) within a diphosphine ligand is necessary to achieve good catalytic activity in keto group hydrogenation reactions. Thus, a three- or four-carbon diphosphine backbone tends to afford much more active catalysts relative to two-carbon-bridged systems . Also, the electronic character of the ligand appears important; more electron-rich (e.g., more highly alkylated) phosphines evoke higher rates in Rh-catalyzed hydrogenation of carbonyl groups. , On the basis of these two concepts, we recently developed rhodium catalysts based upon the achiral ligand 1,1‘-bis(diisopropylphosphino)ferrocene (DiPFc) 9a.…”
Section: Introductionmentioning
confidence: 99%
“…6.17), the hydrogenation of CO to MeOH, hydrogen transfer reactions and alcohol homologation. However, the successful isolation of such complexes from the catalytic systems was very rare [32][33][34][35][36][37]. [38].…”
Section: Complexes Resulting From Activation Of Alcohols: Hydrido(alkmentioning
confidence: 99%